KONSEP ZUHUD MENURUT AL-GHAZALI - Fauzi, Ahmad (Proceeding International Seminar of Islamic Studies, 2024)
Zuhud according to Imam Al-Ghazali is leaving the world because he understands that this world is despicable when compared to the state of the afterlife. Some of the qualities possessed by ascetic people include patience, lack of hasad, qana'ah, tawadhu' and sincerity. Meanwhile, the concept of asceticism in general is an attitude of distancing oneself from everything related to the world. A person who is ascetic should not have his heart shackled or his heart should not be bound by worldly things and not make them his goal.